CORRELATION OF STORAGE SYMPTOMS OR OVERACTIVE BLADDER SYMPTOMS POST TRANSURETHRAL RESECTION OF THE PROSTATE WITH THE DURATION OF CATHETER USE IN A PATIENT WITH URINARY RETENTION DUE TO BENIGN PROSTATE HYPERPLASIA - Perdinan, Alfindy; Alvarino; Ilmiawati, Cimi; Myh, Etriyel (Indonesian Journal of Urology, 2025)
Objective: Find out the correlation of catheter use duration with the incidence of overactive bladder symptoms (OABS) post Transurethral Resection of The Prostate (TURP) in patients with urinary retention due to Benign Prostate Hyperplasia (BPH). Material & Methods: An observational analytical research correlation with a cohort approach was carried out on 29 patients with urinary retention due to BPH post TURP in five hospitals in Padang from January 2019 to August 2019. Data collected included the characteristics and duration of catheter use, which were obtained through interviews using questionnaires, while those of OABS were obtained based on the total score by using the overactive bladder symptoms score (OABSS) standard questionnaire. Results: The average duration of catheter use was 14.9 ± 8.0 days, and the average total OABSS score was 4.7 ± 2.5. Bivariate analysis results showed a positive correlation with a weak strength between the duration of catheter use and the total OABSS score (Pearson’s correlation, r = 0.396, p = 0.033). Conclusion: It is necessary to shorten the duration of catheter use to decrease the incidence and severity of OABS in patients with urinary retention due to BPH post TURP. Keywords: Benign Prostate Hyperplasia, duration of catheter use, overactive bladder, urinary retention.